OTONOMI DAERAH DAN KORUPSI - NORSANTI (Journal Ilmu Sosial, Politik, dan Ilmu Pemerintahan, 2015)
The regional autonomy policies generally appear because of bad implementation from government machine. It does not go from local society and small society needs. The regional disatisfaction to the government also is encouraged by massively exploitation of natural resources that occure in regoins that have many natural resources, but there is not optimalization of holding development in the region. However, in the fact, since the regional autonomy is applied in 1999 until now the wishes of society in order to get optimalization of holding development in a region are not implemented even, the moving of corruption is occurred from central toregions. Islam has an unique method to prevent corruption in a region. In Islamic government (khilafah), there is not regional autonomy because the from  of islamic state is a united state. A governor (wali) is elected by khalifah directly, it also occures in smaller regions. Wali is not elected by citizens and DPRD because there is not DPRD in khilafah state. The directly pointing makes candidates of governor do not need confuse to prepare a lot of donation for campaign or bribe citizens in order to choose them until they do not need fund in jection from others (enterpreneur). In addition, the moneter policies in khilafah system also follow sentralization principle, that very different with fiscal desentralization in the regional autonomy in khilafah system, donation from the whole regions is pulled by central region to distribute to each regions based their needs. It doesn?t distribute based on the amount of incomes.